Bacterial content of the human pancreatic duct: An observational study. Issue 11 (November 2022) - Demir, Elke; Yilmaz, Bengi Su; Jäger, Carsten; Rothe, Kathrin; Schorn, Stephan; Pergolini, Ilaria; Göß, Rüdiger; Safak, Okan; Wilhelm, Dirk; Martignoni, Marc E.; Novotny, Alexander R.; Friess, Helmut; et al.
Abstract: Background: Pancreatic fistula/PF is a challenging surgical complication. We could recently show that intestinal bacteria such as Enterobacterales colonize the PF fluid even after a "sterile" operation like distal pancreatectomy/DP. Therefore, we explored the bacterial flora of the human pancreatic duct in a patient collective undergoing pancreatic surgery. Methods: In this observational study, upon transection of the pancreas during surgery, a swab was inserted into the main duct, and the micro-organismal content was correlated with clinical characteristics. Results: Between February 2017 and February 2020, an intraoperative swab from the pancreatic duct was obtained from a total of 54 patients who underwent pancreatico-duodenectomy/PD or DP. The swabs were sterile in 39 cases (72.2%), detected intestinal bacteria in 10 cases (18.5%), and other bacteria in 5 cases (9.3%). There was no correlation of the micro-organismal content of the pancreatic duct swab with bacteria detected in the PF fluid or bile. Preoperative ERCP was associated with a higher frequency of bacterial colonization of the pancreatic duct (33.3% vs. 6.7%, p = 0.005). There was no correlation of the pancreatic duct swabs with postoperative complications. Discussion: The human main pancreatic duct is usually sterile, and its bacterial colonization does not correlate with the occurrence of PF. Therefore, the mechanisms leading to infection of PF warrant in-depth, mechanistic investigation. Abstract : Bacteria; Enterobacterales; Pancreatic surgery; Pancreatic duct; Fistula; Complications.